Feeding Practices in Small Holder Production System by Dairy Farmers of Meerut District, Uttar Pradesh (Indian Journal of Animal Production and Management, 2025)
A study was conducted in small holder production system to understand feeding  practices of dairy farmers of Meerut district. 100 farmers having land holding up  to 4 acres were selected randomly, 50 from rural and 50 from urban area of the  district. A suitable interview schedule was developed for these farmers to record  the observations. The study revealed major differences in rearing preferences of  dairy farmers based on family and caste system in urban and rural area. Majority of  dairy farmers had good experience in dairy farming with moderate income status.  Significant differences were observed in feeding of roughages and concentrate to  animals, formulation of concentrate and method of feeding concentrate to animals  in the study area. Improved feeding techniques such as urea treatment, conservation  of feed and fodder as hay and silage were less popular in both the areas of the study.  The major limitations included problems related to infertility in animals, lesser  knowledge of technology driven practices and unavailability of veterinary laboratory  testing facilities in the area.
Keywords: Dairy farmers; Land holding; Production system; Income